Cities, Universities and Civilization - Jackson, Murray ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
To fully understand and appreciate urban colleges and universities, it is essential to be aware of and sensitive to the urban environment. The urban university shares both the advantages and the problems of its surrounding city. The cultural institutions and the diverse population of the city are invaluable resources which, inevitably, embody aspects of the problems and challenges confronting urban areas. In spite of these links, little is known about the nature of the exchange between the urban college or university and its environment. Relevant questions touch on (1) the general nature of the urban environment, especially as it influences the university; (2) the areas of the urban environment that are relevant to higher education and are affected by it; (3) the pattern of the relationships between the university and its environment; (4) the impact of the various relationships on the university; and (5) the impact and influences of the relationships, activities, and programs on the urban environment. In Detroit, Michigan, answers to these questions might be most effectively formulated through the development of a consortium of Detroit's institutions of higher education and cultural institutions that can work for the benefit of the entire community, and allow for the development of new dimensions in learning. (CMG)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Colleges; Consortia; Cooperative Programs; Cultural Centers; Higher Education; Institutional Cooperation; Interaction; School Community Relationship; Urban Areas; Urban Culture; Urban Environment; Urban Universities; Opinion Papers